Patency rates of hepatic arterial resection and revascularization in locally advanced pancreatic cancer. Issue 11 (November 2022) - Alva-Ruiz, Roberto; Abdelrahman, Amro M.; Starlinger, Patrick P.; Yonkus, Jennifer A.; Moravec, David N.; Busch, Joel J.; Fleming, Chad J.; Andrews, James C.; Mendes, Bernardo C.; Colglazier, Jill J.; Smoot, Rory L.; Cleary, Sean P.; et al.
Abstract: Background: Arterial resection (AR) for pancreatic adenocarcinoma is increasingly considered at specialized centers. We aimed to examine the incidence, risk factors, and outcomes of hepatic artery (HA) occlusion after revascularization. Methods: We included patients undergoing HA resection with interposition graft (IG) or primary end-to-end anastomoses (EE). Complete arterial occlusion (CAO) was defined as "early" (EO) or "late" (LO) before/after 90 days respectively. Kaplan–Meier and change-point analysis for CAO was performed. Results: HA resection was performed in 108 patients, IG in 61% (66/108) and EE in 39% (42/108). An equal proportion (50%) underwent HA resection alone or in combination with celiac and/or superior mesenteric artery. CAO was identified in 18% of patients (19/108) with arterial IG least likely to occlude (p= 0.019 ). Hepatic complications occurred in 42% (45/108) and correlated with CAO, symptomatic patients, venous resection, and postoperative portal venous patency. CAO-related operative mortality was 4.6% and significantly higher in EO vs LO ( p  = 0.046). Median CAO occlusion was 126 days. With change-point analysis, CAO was minimal beyond postoperative day 158. Conclusion: CAO can occur in up to 18% of patients and the first 5-month post-operative period is critical for surveillance. LO is associated with better outcomes compared to EO unless there is inadequate portal venous inflow.